The Relationship between Teenage Pregnancy and Baby's Birth Weight: Hubungan Kehamilan Remaja Terhadap Berat Lahir Bayi - Tempali, Sri Restu; Mangun, Mardiani; Kusika, Sri Yanti; Silfia, Niluh Nita; Usman, Hastuti; Stibis, Yovita Febri (Poltekkes Kemenkes Palu, 2024)
Background: Teenage pregnancy causes various negative health and socio-economic impacts for the mother and unborn child. Data on cases of babies born to teenage mothers at the Pantoloan Community Health Center in 2021-2022 were 51 people. Objective: To determine the relationship between teenage pregnancy and baby birth weight in the Pantoloan Community Health Center Area. Method: The research used is a cross-sectional study. This research was carried out from 21 s.d. August 28 2023, in the Pantoloan Community Health Center working area. The research population was 51 babies, the sample in this study was the total population. The data collection technique is secondary data using univariate and bivariate analysis. The statistical test used was Chi-square using SPSS. Results: The research results showed that 1 person (8%) was pregnant at the age of 13-15 years in the LBW birth category and none in the LBW birth category. Of teenagers who became pregnant at the age of 16–19 years, there were 11 people in the LBW birth category (92%) and 39 people in the LBW birth category (100%). The results of the analysis have a P-value of 0.069 (< 0.05). Conclusion: There is no relationship between teenage pregnancy and baby birth weight in the Pantoloan Community Health Center area, Palu City. It is hoped that it can increase education among teenagers about child marriage